Preferensi dan pencarian pakan lebah tanpa sengat pada berbagai tipe penggunaan lahan di Pulau Lombok - Septiantina Dyah Riendriasari; Damayanti Buchori; Purnama Hidayat (Perhimpunan Entomologi Indonesia, 2022)
Availability of sufficient feed ensures the success of the stingless bee’s keeping. One of the foods utilized is pollen. Pollen is powder which produced by male genitalia on flowers and contains protein, vitamins, and minerals needed by bees. The aims of this study is looking for preferences and searching for feed through the identification of pollen at stup and studies the flight range to find food. This research was conducted in 26 villages in four districts on the Lombok island during November 2017 until February 2018. Determination of the sample was carried out using the snowball information method to get 26 farmers and 1.57% stup taken as samples on three different types of land use, there are agroecosystems, forests, and settlements. Pollen samples are taken directly and analyzed by acetolysis and identified in the laboratory. Potential feed were observed directly through plant’s identification that are located within a radius of 500 meters from the hive. The results showed that the stingless bee’s feed from the Bromeliaceae and Cyperaceae in all types of land use. The Liliaceae is a potential feed in the agroecosystem, while Asteraceae is a potential feed in residential and forest land. Stingless bee that are cultivated in agroecosystem tend to look for food around a radius of 500 m, in forest foraging for food outside the radius and in settlement have a 50% tendency to look for food within a radius. This information is expected to be beneficial for the stingless bee’s beekeeping, especially in Lombok Island.